Investigations on an active pre-chamber ignition system in a combustion chamber - Russwurm, Tim; Peter, Andreas; Strauß, Lukas; Rieß, Sebastian; Wensing, Michael (International Journal of Engine Research, 2022)
Pre-chamber ignition systems are one way to enable homogeneous lean or dilute combustion. Both strategies can significantly increase the efficiency of spark ignition engines. Spark initiated combustion in the pre-chamber produces hot gases that rapidly enter the cylinder and ignite the diluted charge at multiple points. Active ignition systems with fuel in the pre-chamber can directly influence the composition of the pre-chamber to ensure good ignition properties and sufficient ignition energy. This paper shows results from a novel test facility that enables investigations on the jet propagation of an active pre-chamber inside a constant pressure vessel. Thereby, the background mixture inside the vessel is variated between lambda = 1.0 and lambda = 2.0. With a special designed single-hole pre-chamber the flame propagation of a single pre-chamber jet is measured both in direction of the transfer port and perpendicular to this direction. Compared to spark ignition under equal ambient conditions (350 degrees C, 10 bar), the pre-chamber combustion propagates around eight times faster in direction of the transfer port and 60% faster in radial direction. Until lambda = 1.6, the flame propagation speed in radial direction can be kept on the level of a stoichiometric spark ignition. The simultaneous record of OH*-chemiluminescence and high-speed Schlieren imaging shows that the dominant ignition mechanism of a passenger-car sized pre-chamber is jet ignition according to the classification of Biswas. In stoichiometric cylinder conditions, a rich pre-chamber hampers the ignition in the main chamber whereas in lean operation points the scavenging of the pre-chamber with a rich lambda = 0.8 mixture is beneficial. These measurements indicate how the disrupted flame front of a pre-chamber jet increases the turbulence and enhances the flame propagation. The highest recorded propagation speed occurs in stoichiometric conditions both in the pre-chamber and in the combustion module.
CRIS-Team WoS Importer:2022-09-09